Juridical analysis of the application of the code of ethics to notaries who commit occupational violations - Jumianto Jumianto; Ali Amran; Erniyanti Erniyanti (Annals of Justice and Humanity, 2025)
Purpose: This study aims to analyze the legal arrangements governing the Notary code of ethics in Indonesia, particularly in Tanjungpinang City, examine its practical application in cases of office violations, and identify the obstacles and solutions in enforcing professional discipline. Methodology: The study applies normative and empirical juridical approaches, using legal reviews of the Notary Position Law and INI Code of Ethics, supported by interviews, documentation, and field observations of supervisory practices by the Regional Supervisory Assembly and the INI Honor Council in Tanjungpinang City. Results: The study finds that although notarial ethical regulations are comprehensive, practical enforcement remains inconsistent due to persistent violations, low ethical awareness, weak coordination, and limited public legal literacy. Conclusions: The enforcement of the notarial code of ethics in Tanjungpinang City is still suboptimal despite sufficient normative frameworks. Effective enforcement requires strengthening institutional coordination, raising public awareness, and conducting periodic evaluations of ethical regulations. Limitations: This research is geographically limited to Tanjungpinang City and primarily focuses on current supervisory mechanisms. Broader comparative studies across different regions could provide deeper insights into systemic issues in notarial supervision. Contribution: The study contributes to the discourse on professional accountability in the notarial field by highlighting the gap between normative regulation and empirical practice. It also provides recommendations for improving institutional oversight and public legal awareness, thereby enhancing legal certainty and professional integrity in notarial services.